The Curtain Sign in Lung Ultrasound - Lee, Francis Chun Yue (J Med Ultrasound, 2017)
The curtain sign (CS) is a sonographic artifact found in lung ultrasound studies. It is generally used to describe the appearance of an expanded and aerated lung, often in the context of pleural effusion diagnosis. In emergency and critical care ultrasound use, the recognition of changes to the CS is very useful in the detection of early pulmonary pathological processes occurring at the lateral lung bases and costophrenic recesses. The author suggests a simple standardisation of the CS description and describes its use in lung ultrasound.